ChemInform Abstract: Copper on Iron: Catalyst and Scavenger for Azide—Alkyne Cycloaddition. Issue 19 (18th April 2013) - Kovacs, Szabolcs; Zih‐Perenyi, Katalin; Revesz, Adam; Novak, Zoltan
Abstract The Fe amount not only behaves as support for Cu but also represents a redox scavenger and reduces the copper contamination of the organic products.